Hepatitis B virus infection and factors associated with its acquisition among adults in a Lake Victoria HIV hyperendemic fishing community in Kyotera district, Uganda: a cross-sectional observation. Issue 4 (7th April 2022) - Ssuuna, Charles; Ssempijja, Victor; Kalibbala, Sarah; Serwadda, David; Yeh, Ping Teresa; Wawer, Maria; Gray, Ronald; Chang, Larry; Kagaayi, Joseph; Reynolds, Steven
Abstract : Objective: To investigate hepatitis B virus (HBV) prevalence and factors associated with viral acquisition in a HIV-hyperendemic fishing community, we tested sera for anti-hepatitis B core (HBc) and hepatitis B surface antigen (HBsAg). Design: Observational cross-sectional study. Setting: Large fishing village on Lake Victoria, one of the HIV-hyperendemic Rakai Community Cohort Study (RCCS) sites (HIV prevalence 40%). Participants: Sample of 460 RCCS participants aged 15–49 years from survey conducted from 5 December 2016 to 13 February 2017. These proportionately included HIV-negative, HIV-positive antiretroviral therapy (ART)-naïve and HIV positive on ART participants. Results: Of the 460 participants, 49.6% (95% CI 45.0% to 54.1%) had evidence of prior HBV infection and 3.7% (95% CI 2.3% to 5.9%) were either acutely or chronically infected. HBV risk increased with age, number of lifetime sex partners and HIV seropositivity. HBV risk decreased with HIV ART use among HIV-positive participants. Prevalence of prior HBV infection was 17.1% in participants aged 15–19 years, 43.2%, 55.3% and 70.1% in participants aged 20–39, 30–39 and 40–49 years, respectively (p<0.001). Additionally, the prevalence of prior HBV infection was 23.8% in participants with 0–1 lifetime sex partners, 43.2% and 54.8% in participants with 2–3 lifetime sex partners and 4+ lifetime sex partners, respectively (p<0.001). Conclusions: Findings from this fishing community suggest the need to provide HBV vaccination to adults at risk of sexual transmission who have not been previously immunised.